Influence of innovative culture on state development. Ukrainian and Norwegian experience - Vershytsky, A.V.; Putintseva, M.V. (Культура народов Причерноморья, 2013)
The purpose of the research is determination of the influence level of innovative culture on the state development on the example of Ukraine and Norway and the tendencies reveal of the innovation culture of society, as a factor of innovation activity in the state. This research describes essence of innovative culture as a whole, its influence on the innovative processes and compares differences in governments’ approaches to supporting innovative activity in Ukraine and Norway. The authors used such methods of studies as synthesis, idealization, induction and deduction, mental simulation, etc. The main findings are that innovative culture of society is one of the key aspects that directly influence on the economic indicators. Целью исследования является определение уровня влияния инновационный культуры на государственное развитие на примере Украины и Норвегии и выявление особенностей инновационной культуры общества, как фактора инновационной активности государства. Эта статья описывает сущность инновационной культуры в целоем, её влияния на инновационные процессы и сравнение различий в государственных подходах к поддержке инновационной активности в Украине и Норвегии. Были использованы такие методы исследования как синтез, индукция и дедукція, анализ и т.п. Основными выводами стало то, что инновационная культура общества – это один из ключевых аспектов, оказывающих прямое воздействие на экономические индикаторы. Головна мета цієї роботи – це визначення рівня впливу інноваційної культури на державний розвиток на прикладі України та Норвегії, а також виявлення особливостей інноваційної культури суспільства, як фактора інноваційної діяльності держави. Ця стаття відображає інноваційну культуру загалом, її вплив на інноваційні процеси, а також порівняння відмінностей в державних підходах до підтримки інноваційної діяльності в Україні та Норвегії. Були використані такі методи дослідження, як синтез, індукція, дедукція, аналіз та інші. Основним висновком є те, що інноваційна культура суспільства – це один з ключових факторів, який прямим чином впливає на економічні індикатори.